2004
DOI: 10.1055/s-2004-860951
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Solitary Fibrous Tumor Arising from the Anterior Cranial Fossa

Abstract: The solitary fibrous tumor (SFT) is a mesenchymal, spindle cell neoplasm that was originally found in pleural tissue. Recently, however, numerous extrapleural sites have been discovered, including the nasal cavity. We present the 15th case of a nasal SFT, and the first such tumor to arise from the cribriform plate and extend into the anterior cranial fossa. In addition to highlighting the aggressive nature of this tumor, we review its clinical features and the diagnostic difficulties posed by SFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 19 publications
(24 reference statements)
0
43
0
Order By: Relevance
“…12,15 SFTs typically develop in the sinonasal cavity but may show evidence of local extension into the orbit, pterygopalatine and infratemporal fossa, skull base, or intracranial cavity. 6,11 Dynamic contrast-enhanced MR imaging may aid in the specific diagnosis of head and neck lesions and predicts their biologic behavior. 21,22 TICs of the 4 patients in the present study showed a washout pattern (type III), which is similar to that of the internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,15 SFTs typically develop in the sinonasal cavity but may show evidence of local extension into the orbit, pterygopalatine and infratemporal fossa, skull base, or intracranial cavity. 6,11 Dynamic contrast-enhanced MR imaging may aid in the specific diagnosis of head and neck lesions and predicts their biologic behavior. 21,22 TICs of the 4 patients in the present study showed a washout pattern (type III), which is similar to that of the internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…SFTs of the sinonasal cavity are rare, with fewer than 30 cases reported in the English literature to date. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Although several case reports and clinical studies have mentioned imaging findings of SFTs in this region, 6,12,15 the specific imaging characteristics of sinonasal SFT have not been detailed in the literature. We present the CT and MR imaging features of 5 patients with sinonasal SFTs proved by histopathology.…”
mentioning
confidence: 99%
“…1 In head and neck region SFT may involve meninges, oral cavity, orbit, soft tissue of head and neck, upper respiratory tract, nasal cavity, paranasal sinuses, salivary glands, thyroid, parapharyngeal space and tongue. [1][2][3][4] The first case in the English literature of a solitary fibrous tumor arising in nasal cavity was reported by String fellow in 1996 in a 59 year old woman. 13 In a review of literature, Alobid et al 14 have mentioned 21 cases of primary SFT arising in nasal cavity and paranasal sinuses.…”
Section: Disscusionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Today SFT is described as a "mesenchymal" tumor [1][2][3][4][5][6][7][8][9][10][11][12] as most investigators believe that their origin is mesenchymal, as evident by their fibroblastic differentiation histopathologically, immunohistochemically and ultrastructurally. 3,4 This fact also explains the occurrence of SFTs at numerous extrapleural sites. Extrapleural SFT is a rare entity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation